THE INFLUENCE OF PROMOTION, WORD-OF MOUTH, AND BRAND IMAGE ON CONSUMER PURCHASE DECISIONS: A STUDY OF KOPI SOE MEDAN: Promotion, Word-of Mouth, Brand Image, Purchase Decisions, Coffe Shop Industry - Carissa Emily Wijaya; Afrizal; Lisa Elianti Nasution (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the influence of promotion, word of mouth, and brand image on consumer purchase decisions at Kopi Soe Medan. The research employs a quantitative approach using primary data collected through questionnaires distributed to 160 respondents. Data analysis is conducted using multiple linear regression with the assistance of statistical software, including classical assumption tests, t-tests, F-tests, and the coefficient of determination (R²). The results show that partially, promotion, word of mouth, and brand image each have a positive and significant effect on purchase decisions. Simultaneously, all independent variables also have a significant effect on purchase decisions, indicating that the model is statistically valid. Among the variables, brand image has the strongest influence, followed by word of mouth and promotion. The coefficient of determination indicates that the model explains a moderate proportion of the variation in purchase decisions, while the remaining variance is influenced by other factors. These findings suggest that strengthening brand image, optimizing promotional strategies, and encouraging positive word of mouth are essential for improving consumer purchase decisions. Therefore, an integrated marketing strategy is necessary for businesses to remain competitive in the coffee shop industry.